2021
DOI: 10.1007/s40262-021-01051-9
|View full text |Cite
|
Sign up to set email alerts
|

Perpetrator Characteristics of Azole Antifungal Drugs on Three Oral Factor Xa Inhibitors Administered as a Microdosed Cocktail

Abstract: Background Factor Xa inhibitors (FXaIs) are increasingly used without having sufficient drug-drug interaction data. Using a microdosed cocktail methodology could support filling the knowledge gap quickly. Methods In a randomised crossover trial, we investigated the drug-drug interactions between six oral azole antifungals and a microdosed FXaI cocktail containing 25 µg rivaroxaban, 25 µg apixaban, and 50 µg edoxaban. Additionally, different enzyme activities were also monitored using a microdosed cocktail appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…Because we assessed patients who were actively hospitalized, bleeding risk may have been increased due to factors that could not be fully assessed retrospectively (e.g., endothelial injury). However, the rates of bleeding observed in our study were consistent with what was expected based on prior literature 13–17 . Additionally, the duration of concomitant administration of fluconazole with DOAC was short at 4 days (IQR 3–7), which may have impacted the number of bleeding events based on the expected drug–drug interaction.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Because we assessed patients who were actively hospitalized, bleeding risk may have been increased due to factors that could not be fully assessed retrospectively (e.g., endothelial injury). However, the rates of bleeding observed in our study were consistent with what was expected based on prior literature 13–17 . Additionally, the duration of concomitant administration of fluconazole with DOAC was short at 4 days (IQR 3–7), which may have impacted the number of bleeding events based on the expected drug–drug interaction.…”
Section: Discussionsupporting
confidence: 88%
“…The study conducted in Taiwan found an increased risk of major bleeding in patients with nonvalvular atrial fibrillation with concomitant fluconazole and DOAC use (adjusted incidence rate 2.35 overall, 2.26 with dabigatran, 2.25 with rivaroxaban, and 3.36 with apixaban) 7 . The study unexpectedly found no increased bleeding risk with other azole antifungals that are more potent CYP3A4 inhibitors (voriconazole and posaconazole) compared with fluconazole 7,9,17 . This study was limited to patients with nonvalvular atrial fibrillation, whereas our study included both patients with atrial fibrillation and VTE.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…An oral microdose DOAC cocktail (µ-FXaI) containing apixaban (25 µg), edoxaban (50 µg) and rivaroxaban (25 µg) has been successfully used in adults to study drug–drug interactions 5 6. Comparing the PK of these 3 µ-FXaI, obtained after simultaneous administration, with the PK after therapeutic DOAC doses from the literature showed DOAC clearances always in the same range (dose-proportional PK) 7–9.…”
Section: Introductionmentioning
confidence: 99%
“…The edoxaban plasma concentration increases with the co‐administration of verapamil, amiodarone, and azole antifungals (Mendell et al., 2013; Mikus et al., 2020; Rohr et al., 2022). Moreover, a drug–drug interaction study demonstrated that cyclosporine at a single oral dose of 500 mg dramatically elevated not only the maximum plasma concentration of edoxaban (245.7 ng/mL vs. 410.9 ng/mL) via the inhibition of P‐glycoprotein but also that of the active metabolite of edoxaban (M4) (23.2 ng/mL vs. 191.1 ng/mL) via the inhibition of organic anion transporter 1B1 (OATP1B1) (Parasrampuria et al., 2016).…”
Section: Introductionmentioning
confidence: 99%